Rite of passage - Wright, Richard, 1908-1960. (New York : HarperCollins Publishers, 1994)
When fifteen-year-old Johnny Gibbs is told that he is really a foster child, he runs off into the streets of Harlem and meets up with a gang that wants him to participate in a mugging. Includes criticism of Wright's fiction.
Includes bibliographical references (p. [145]).
Keywords: African American teenage boys -- Fiction; Gangs -- Fiction; Runaways -- Fiction; Gangs -- Fiction; African Americans -- Fiction; Harlem (New York, N.Y.) -- Fiction; Harlem (New York, N.Y.) -- Fiction; Bildungsromans